A CLOSER VIEW ON ANCIENT MEMORIAL OF YUSUF KHOS HAJIB “KUTADGU BILIG” - Botirova , Zebo Xakimjon Kizi; Asadova, Rayxon Izatulla Qizi (Educational Research in Universal Sciences, 2023)
“Kutadgu Bilig” has been translated into many languages of the world. In particular, translations into Western European languages are also very important. The work was translated into English for the first time by University of Chicago professor Robert Denkoff in 1983 and for the second time by English poet and translator Walter May in 1998. The history of the study of the work can be a separate object for a number of studies. It is worth noting that so far there have been several attempts in this direction. Through this article, it will be possible to get acquainted with such studies